Topical Microbicides for the Prevention of Sexually Transmitted Diseases and HIV - André Désormeaux; Rabeea F Omar; Michel G Bergeron (Canadian Journal of Infectious Diseases)
The development of novel compounds to reduce the sexual transmission of human immunodeficiency virus (HIV), herpes and other pathogens causing sexually transmitted diseases (STDs) has become a topic of great interest. Condom use is the only readily available measure to reduce successfully the propagation of these infectious agents. To reduce significantly the probability of acquiring infection, condoms should be used during all risky sexual intercourse. More attention is being given to female-controlled methods for the prevention of HIV infection because many women are unable to negotiate condom use with their sexual partners. The development of topical microbicides constitutes one of the most priori tized research areas in the field of prevention of STDs/HIV for the World Health Organization, the National Institutes of Health and the Centers for Disease Control and Prevention. Because the number of women infected with HIV, herpes and other pathogens causing STDs is growing dramatically worldwide, there is an urgent need to develop innovative preventive measures that can reduce the transmission of these pathogens with minimal mucosa! irritation, and minimal effects on the vaginal flora and pH. Some of the existing products as well as promising new topical microbicicles for the prevention of sexually transmitted infections are reviewed.